(untitled) (The Research of Medical Science Review, 2025)
Introduction: Dentists provide treatments spanning oral health exams, pain relief, aesthetics, and functional restoration. Dental colleges deliver thorough care via supervised student practitioners, prioritizing excellence. In order to provide the appropriate health-care services to patients, it is essential to investigate their health-care needs, and expectations. Aims & objectives: This study aims to evaluate how satisfied patients are with the dental facilities, services and the level of care they receive by dental house officers to improve the quality of care being provided. Methodology: A questionnaire-based survey quantified factors impacting satisfaction from different departments. Anonymity was ensured in the questionnaire to secure participant privacy. Result: A total of 250 questionnaires were distributed, and 206 responses were received. The findings revealed a very high level of overall satisfaction among the participants, indicating strong contentment with the treatment received. Majority of the patient were satisfied with the Oral Surgery department as compare to other departments. The treatment received unanimous satisfaction, highlighting that patient satisfaction was consistent across gender, age, and departments at the dental clinic. Conclusion: Our study found that patients are very satisfied with the care provided by dental house officers, reflecting their dedication to quality and patient needs. However, there were few dissatisfied patients, so it’s important to improve care quality. Providing excellent patient experiences can attract and keep more patients, benefiting dental house officers and the institute as a whole.